Peran Perpustakaan Masjid dalam Meningkatkan Literasi Keagamaan di Masjid Dirgantara: The Role of the Mosque Library in Increasing Religious Literacy at the Dirgantara Mosque - Harahap, Fadila Aldina; Faturrahman, Muslih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The library as a source of information services includes activities of processing, collecting, presenting, disseminating and preserving information. The library is one of the efforts to maintain and improve the efficiency and effectiveness of the teaching and learning process. Establishing a library in a mosque is the right step to achieve this goal by creating a center of knowledge that can improve the congregation's understanding of the importance of harmony in community life. The library at the Dirgantara Mosque has an important role in facilitating harmony among religious communities. This facility not only functions as a place to increase knowledge and interest in reading, but also as an effort to increase the level of community literacy. With effective management, this library can be a resource that motivates the community to use it, which in turn will contribute to increasing intellectuality and social development. This study uses descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the existence of a library at the Dirgantara Mosque plays a role in providing religious literature and also general literature for mosque visitors. The provision of various literature is intended to increase the insight of Muslims from various reference sources. In addition, the existence of a library in the mosque area allows mosque visitors to have other activities while waiting for prayer times. The library at the Dirgantara Mosque also has 6 shelves of religious literature such as Islamic Fiqh, Creed and Morals, Practices and Prayers.